Effects of dietary glutamine and arginine supplementation on performance, intestinal morphology and ascites mortality in broiler chickens reared under cold environment - Abdulkarimi, Rahim (Asian-Australas J Anim Sci, 2019)
OBJECTIVE: An experiment was conducted to evaluate the effects of dietary glutamine (Gln) and arginine (Arg) supplementation on performance, intestinal morphology and ascites mortality in broilers. METHODS: A total of 675 day old chicks were randomly allocated to 9 experimental groups in a 3×3 factorial arrangement based on a completely randomized design with 5 replicates of 15 chicks. Three levels of dietary Gln (0%, 0.5%, and 1%) and Arg (100%, 130%, and 160% of Ross recommendation) supplementation were used in ascites inducing condition (15°C ±1°C) from 7 to 42 days of age. RESULTS: Dietary supplementation of Gln increased body weight gain during grower, finisher and total periods (p<0.05) and increased feed intake during total period. Ascites mortality was decreased by Gln supplementation (p<0.05). Gln supplementation increased the villus height (VH) and crypt depth (CD) in duodenum and jejunum (p<0.05). Arg supplementation decreased CD in duodenum and jejunum, and increased ileum villus width (VW) and also VH/CD ratio in duodenum and jejunum (p<0.05). Both Gln and Arg increased the goblet cell number (GCN) in duodenum whereas Gln supplementation decreased GCN in jejunum and ileum (p<0.05). The Gln×Arg interaction were observed for right ventricle (RV)/total ventricular (TV) ratio, VH, VW, CD, VH/CD. CONCLUSION: It was concluded that dietary 0.5% Gln alone or along with 130% Arg of Ross requirement, improve the intestinal morphology and performance and hence decrease the ascites mortality in broiler chickens with cold induced ascites.